Równania hydrodynamiki a modele ekonomiczne - Juzwiszyn, Jacek; Krzywicki, Andrzej (Hydrodynamic Equations - Economic Models?, 2006)
The phenomenon of the appearance of chaotic solutions in deterministic models will be presented on the example of hydrodynamic equations.Can such models help in describing economic models?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 69-76